BACTERIAL VAGINOSIS PREVALENCE IN PREGNANT WOMEN AND ITS RELATION TO PRETERM BIRTH - Shailesh Barbde (Journal of Biomedical and Pharmaceutical Research, 2020)
BACKGROUND: Bacterial vaginosis when symptomatic, presents as the malodorous and increased amount of vaginal discharge, grey to homogeneous white. Early screening, diagnosis, and treatment of bacterial vaginosis in pregnant women are helpful in preventing maternal and fetal complications. The majority of the cases of bacterial vaginosis are asymptomatic, remain unreported, and hence untreated. Bacterial vaginosis has been associated with spontaneous abortions, preterm delivery, premature rupture of membranes, amniotic fluid infections, and postpartum endometritis. It is known to be a strong independent risk factor for adverse pregnancy outcomes Gardnerella vaginalis are gram-negative to gram-variable small pleomorphic rods that are non-motile. Mobil uncus is a gram-negative anaerobic rod-shaped bacterium. AIM: Bacterial vaginosis prevalence in pregnant women and its relation to preterm birth MATERIAL AND METHOD: The study was done in the Department of Obstetrics and Gynecology. Written consent in the patient’s own language was taken. All antenatal women were assessed at the first visit and followed up in the subsequent trimesters. First, detailed history followed by a general and obstetric examination was done. All these women were subjected to routine antenatal investigations. Under aseptic precautions, an unlubricated sterile Sim’s speculum was inserted into the vagina and the type of discharge was noted. If any vaginal discharge was present, its color, amount, and odor were noted. Vaginal pH was evaluated using conventional pH strips. RESULTS: The majority of cases of BV in antenatal women were diagnosed after 28 weeks of gestation. There was a significant association of BV with Preterm, early preterm, premature rupture of membranes, and low birth weight. There was no relation between parity and socioeconomic status with Bacterial Vaginosis. The commonest mode of birth was normal vaginal delivery in BV-positive antenatal women. In the first trimester, none of the pregnant women in our study population developed bacterial vaginosis. Between 12-28 weeks, 11.5% of pregnant women developed bacterial vaginosis. 88.5% of pregnant women developed bacterial vaginosis. Majority of pregnant women with bacterial vaginosis diagnosed by Amsel’s criteria delivered by normal vaginal delivery. CONCLUSION: So to conclude, the results of this study suggest that for reducing the problem of low birth weight, the public health strategy needs to focus on the early detection and treatment of Bacterial Vaginosis. Pregnancy with Bacterial Vaginosis should be monitored more closely. Pre-pregnancy maternal genital hygiene has to be emphasized. Bacterial vaginosis needs to be screened and managed timely to reduce the death rates of our premature and low-weight newborns. KEYWORDS: Bacterial vaginosis, premature rupture of membranes, spontaneous abortions